Chronic Abdominal Pain on Lumbar Osteophyte Aabout a Case - Synèse, Bemora Joseph; Herman , Herilantoniaina Julien; Emilien , Rabezanahary Jean; Lalaina Andrianina, Rabemazava Alexandrio Zo; Jean Claude , Razafimahandry Henri; Clément, Andriamamonjy (International Journal For Research In Health Sciences And Nursing, 2020)
Lumbar osteoarthritis is a degenerative disease that manifests as low back pain. We report the case of a 52 years old patient with an atypical manifestation of lumbar osteoarthritis characterized by chronic abdominal pain. The CT scan showed an anterior osteophytosis at the L3L4 level that causes abdominal pain. He was operated on anteriorly by midline laparotomy for excision of osteophytosis with operative follow-up, marked by a complete disappearance of the pain in the immediate post-operative period.